The Effect of 2 Weeks of Inactivated Probiotic Bacillus coagulans on Endocrine, Inflammatory, and Performance Responses During Self-Defense Training in Soldiers. Issue 9 (September 2019) - Hoffman, Jay R.; Hoffman, Mattan W.; Zelicha, Hila; Gepner, Yftach; Willoughby, Darryn S.; Feinstein, Uri; Ostfeld, Ishay
Abstract : Abstract: Hoffman, JR, Hoffman, MW, Zelicha, H, Gepner, Y, Willoughby, DS, Feinstein, U, and Ostfeld, I. The Effect of 2-Weeks of Inactivated Probiotic Bacillus coagulans on Endocrine, Inflammatory and Performance Responses During Self-Defense Training in Soldiers. J Strength Cond Res 33(9): 2330–2337, 2019—The effect of 2 weeks of inactivated Bacillus coagulans (iBC) ingestion on performance and inflammatory cytokines was examined during a self-defense course in soldiers. Sixteen male soldiers were randomly assigned to either iBC ( n = 8) or placebo (PL; n = 8) in this double-blind study. Participants were garrisoned on base and participated in the same training tasks. Assessments were conducted in a single day before (PRE) and after the supplementation period (POST). During each testing session, participants were assessed for vertical jump power (VJP), muscle endurance, simulated casualty drag, and 2 100-m shuttle runs. Resting blood measures for testosterone, cortisol, creatine kinase, and inflammatory cytokines were also assessed. Mann-Whitney analysis of change (Δ) scores indicated no significant change ( p 's > 0.05) in any of the performance or blood variables. However, a trend ( p = 0.089) was noted in the Δ score for VJP in iBC compared with PL. In addition, trends were observed in the change in IL-10 ( p = 0.057) and IFNγ ( p = 0.057). Magnitude based inferential analysis indicated that changes in VJP and simulated casualty drag were likely beneficial (90.7 and 80.4% likelihood effect, respectively) for iBC. In addition, iBC supplementation very likely augmented IL-10 concentrations, but was possibly negative for changes in IL-6, and likely negative for changes in TNFα and IFNγ. Changes in all other performance and blood markers were unclear. Results indicated that 2 weeks of iBC supplementation appeared to be beneficial for maintaining power and short-term speed performance, while attenuating the inflammatory response during intense training in a military self-defense course.